SYMBOL PRESERVATION AND IDENTITY OF GARUT CITY - Kunto Sofianto; Agusmanon Yuniadi; Agus Nero Sofyan; Budi Gustaman (Sosiohumaniora, 2021)
This article discusses the symbols and identity of Garut City, especially with regard to heritage buildings that were established since the Dutch colonial period. These buildings are very important to be maintained so that the identity of the Garut community is not eroded by the increasingly strong current of globalization. The research method used in this research is a qualitative research method with a historical approach. In addition, the concept of conservation is also used which refers to physical and non-physical aspects and adaptive re-use theory. The conclusion from this research is that various infrastructures, especially the buildings at the beginning of the establishment of Garut city are symbols and identities for the Garut people. The conclusion of this study is that the buildings are very important to be preserved so that they could be proud of by the people of Garut city or the people of Garut regency in general. Thus the Garut people will not lose direction in building a whole human. In addition, the Garut community will understand the importance of buildings in Garut city as a symbol or identity of the Garut community.